2012
DOI: 10.3109/15563650.2012.745939
|View full text |Cite
|
Sign up to set email alerts
|

The difference in C-reactive protein value between initial and 24 hours follow-up (D-CRP) data as a predictor of mortality in organophosphate poisoned patients

Abstract: The initial serum C-reactive protein and acetylcholinesterase were not found to be associated with the severity of acute organophosphate poisoning. However, the difference in C-reactive protein value between initial and follow-up after 24 hours (D-CRP) was associated with mortality in the total population of patients with acute organophosphate poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 12 publications
4
19
1
1
Order By: Relevance
“…This was similar to the results observed by Lee et al (2008) and Yu et al (2012) who mentioned that there were significant differences in heart rate, systolic blood pressure, respiratory rate and body temperature between survivors and non-survivors. Also, this was in agreement with Lee et al (2013) study in which there was significant association between the mortality and decrease in respiratory rate. Severe and refractory hypotension is a leading cause of death in OP poisoning.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was similar to the results observed by Lee et al (2008) and Yu et al (2012) who mentioned that there were significant differences in heart rate, systolic blood pressure, respiratory rate and body temperature between survivors and non-survivors. Also, this was in agreement with Lee et al (2013) study in which there was significant association between the mortality and decrease in respiratory rate. Severe and refractory hypotension is a leading cause of death in OP poisoning.…”
Section: Discussionsupporting
confidence: 93%
“…Bradycardia is recorded more frequently in patients with delayed presentation to the hospital and this finding is strongly associated with mortality (Gündüz et al, 2015). In Lee et al (2013) study there was significant association between the mortality and decrease in respiratory rate which reflect that the respiratory insufficiency is important leading cause of death in OP poisoning. Similarly, Davies et al (2008) reported that GCS was effective at predicting outcome in acute organophosphate poisoning and patients presenting with a GCS ≤ 13 need intensive monitoring and treatment.…”
Section: Discussionmentioning
confidence: 81%
“…A study of OP poisoning patients in the ICU performed by Lee et al found that the mean SOFA score of survivors was 3.9 ± 2.9 and 6.7 ± 2.7 for nonsurvivors. [21] The patients who died in our study had a median SOFA score of 5 while the score of those who survived had a median score of 1.…”
Section: Discussionmentioning
confidence: 64%
“…Mortality rate in the present study was 33.3%. Lee et al, (2013) reported that mortality was 22.9%. However, a 12% death rate was recorded by Sun et al, (2015), he reflected this low mortality to proper atropine administration and close monitoring of intoxicated patients in intensive care unit.…”
Section: Discussionmentioning
confidence: 99%